The wind turbine and the environment interaction model - Boyko Taras; Ruda Maria; Stasevych Serhiy; Chaplyk Olha (Lviv Politechnic Publishing House, 2021)
The modeling of the mutual influence of the wind power plant and the ecosystem is carried out. It is proposed to consider the compartment of a complex landscape complex as an elementary structural element of the ecosystem. The wind power plant is a component of a complex landscape complex and is considered during its life cycle. The categories of environmental impact and the relative contribution of harmful factors for each category have been determined. The modeling was carried out using various scenarios of waste management, which will make it possible to reduce the negative impact of harmful factors for each category. Summary data on the impact of harmful factors on the environment were obtained, and ecological profiles were constructed using the Eco-indicator methodology. Such profiles, together with the weighting factors, allow a comprehensive presentation of environmental impacts and obtaining the values of eco-indicators that characterize the damage caused by a wind turbine to the environment. The process of synthesis of an industrial cyber-physical system is carried out by five typical steps, among which the process of ‘cyber-realization’ is to create a cyber twin and compare it with the real system. To implement this process, mathematical modeling was carried out, as a result of which a system of differential equations was obtained, the input data for which were the values of environmental impacts, expressed by the specified indicators. The resulting model will act as ideal for a real system ‘wind turbine – environment”, and will allow predicting the consequences of the harmful impact of a wind turbine on a complex landscape system and will determine the main impacts to achieve its maximum efficiency and adaptation to the requirements for environmental protection and conservation. Some results obtained using the developed model are presented.
Keywords: Compartment of complex landscape system; Unconventional energy sources; Life-cycle of industrial product; Cyber-twin; Eco-indicators